Effects of organic matter content on the resistivity and pore structure of waste soil - Boxing Yang; Qiang Sun; Xinchao Zheng; Yabin Liu; Jingjing Nan; Jishi Geng (Journal of Applied Geophysics, 2026)

Effects of industrial solid wastes on the rheological behavior and electrical resistivity-acoustic emission responses of cement-based grouted bodies under loading - Xinchao Zheng; Qiang Sun; Fang Liu; Yuhang Li; Boxing Yang; Ran Tang (Journal of Environmental Management, 2026)

Novel green ternary deep eutectic solvents for efficient extraction of nitrogen compounds from oil - Yingying Zuo; Rui Zhou; Xiaohang Yang; Jian Wang; Xu Liu; Yushan Li; Zhengqi Liang; Boxing An; Fengjuan Niu (Journal of Environmental Chemical Engineering, 2026)

Study on the Change Rule and Change Mechanism of the Resistivity and Thermal Conductivity of Food Waste Oil-Contaminated Soil under Different Water Content - Boxing Yang; Qiang Sun; Xinchao Zheng; Yabin Liu; Jingjing Nan (Water, Air, & Soil Pollution, 2026)

Modified Carbon-Based Fe (II)- ZIF Nanomaterials as a Highly-Selective Adsorbent for Phosphate Removal - Xu Liu; Yushan Li; Hao Zhou; Boxing An; Xingyu Yang; Cong Liu; Haiyan Liu; Hai Liang; Zhengqi Liang; Liansheng Li; Guicheng Li; Yingying Zuo (Water, Air, & Soil Pollution, 2025)

Effect of temperature on the radon release characteristics of red clay - Chao Gu; Qiang Sun; Lei Zhang; Liwei Zhang; Duoxing Yang; Boxing Yang; Zhenlong Ge (Journal of Environmental Radioactivity, 2024)

Screening and evaluation of a novel nucleotide-degrading Levilactobacillus brevis grx821 with anti-hyperuricemia ability - Haiying Wang; Jiaxing Dai; Yifeng Han; Yunchao Wa; Dawei Chen; Renqin Yang; Yujun Huang; Hua Wei; Ruixia Gu; Boxing Yin; Wenlong Ma (Food Bioscience, 2024)

Sustainable soil remediation using mineral and hydrogel: field evidence for metalloid immobilization and soil health improvement - Huixia Wang; Liuwei Wang; Boxing Yang; Xuanru Li; Renjie Hou; Zhongtao Hu; Deyi Hou (Journal of Soils and Sediments, 2023)

Effects of PM2.5 and its constituents on hemoglobin during the third trimester in pregnant women - Guilan Xie; Jie Yue; Wenfang Yang; Liren Yang; Mengmeng Xu; Landi Sun; Boxing Zhang; Leqian Guo; Mei Chun Chung (Environmental Science and Pollution Research, 2022)
Anemia has been a public health issue evoking global concern, and the low hemoglobin (Hb) concentration links to adverse pregnancy outcomes. However, the associations of PM 2.5 and its constituents with Hb and anemia in pregnant women remain unclear. In this retrospective birth cohort study, 7932 pregnant women who delivered in the First Affiliated Hospital of Xi’an Jiaotong University from 2015 to 2018 were included. The Hb during the third trimester in pregnant women was assessed before delivery. PM 2.5 and its constituents (BC, NH 4 + , NO 3 − , OM, SO 4 2− , and Dust) during pregnancy were retrieved from the V4.CH.03 product constructed by the Atmospheric Composition Analysis Group. Generalized linear regression model was applied to investigate the effects of PM 2.5 and its constituents on Hb and anemia during the third trimester in pregnant women. The means and standard deviations of PM 2.5 , BC, NH 4 + , NO 3 − , OM, SO 4 2− , and Dust were 69.56 (15.24), 10.02 (2.72), 8.11 (1.77), 14.96 (5.42), 15.36 (4.11), 10.08 (1.20), and 10.98 (1.85) μg/m 3 , respectively. Per IQR increase (μg/m 3 ) of PM 2.5 , BC, NO 3 − , and OM linked to − 0.75 (− 1.50, − 0.01), − 0.85 (− 1.65, − 0.04), − 0.79 (− 1.56, − 0.03), and − 0.73 (− 1.44, − 0.03) g/L decrease of Hb during the third trimester in multiparous pregnant women, but not for NH 4 + , SO 4 2− , Dust, and primiparous pregnant women. PM 2.5 and its constituents had no significant association with anemia, except for Dust (OR: 0.90, 95% CI: 0.82, 0.99, per IQR increase) in primiparous pregnant women. Besides, SO4 2− was of lag effects on Hb and anemia in multiparous pregnant women. Moreover, non-linear associations were found among PM 2.5 and its constituents, Hb, and anemia. Therefore, exposure to PM 2.5 and some constituents of PM 2.5 was associated with reduced Hb level during the third trimester in multiparous pregnant women. Related departments and pregnant women should take targeted actions to eliminate the detrimental effects of PM 2.5 and its constituents on pregnancy outcomes.

RNA binding protein QKI contributes to WT1 mRNA and suppresses apoptosis in ST cells - Xin Liu; Jia Guo; Mengjiao Zhou; Yuwei Yang; Mengdi Liang; Chunyan Bai; Zhihui Zhao; Boxing Sun (Genes & Genomics, 2017)